Eksistensi Jamu Tradisional Berbahan Akar dan Rimpang Tumbuhan di Kota Pekalongan - Diva Nuraini; Gina Marwatul Mutmainah; Agni Fadea Prastita; Giyanti Rika Dwi Pratiwi; Dimas Setiaji Prabowo (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2026)
This study aims to identify the varieties of traditional herbal medicine (jamu) made from plant roots that continue to exist in Pekalongan City and to describe the traditional processing methods employed by the local community. The study adopted a qualitative descriptive approach, with data collected through participant observation, in-depth interviews, and documentation involving jamu vendors, producers, and consumers in the Banjarsari Market area and its surroundings. The findings indicate that root-based jamu is still produced and consumed by the community, particularly in the forms of kunyit asam, beras kencur, ginger, temulawak, cogon grass (alang-alang), temu ireng, galangal, and lempuyang. Each type of jamu serves different health purposes, such as maintaining stamina, stimulating appetite, relieving muscle aches, improving digestion, and supporting physical recovery. The preparation process is generally carried out using simple traditional methods, including boiling, grinding, and filtering the ingredients before consumption. Nevertheless, the sustainability of traditional jamu faces several challenges, including modernization, changing consumer preferences, and the low rate of business succession among younger generations. Therefore, preservation efforts through education, innovation, and support from various stakeholders are essential to ensure that traditional jamu remains sustainable as a cultural heritage and a symbol of the local identity of Indonesian society.